The Effect of Regional Characteristics, Leverage, Government Complexity, BPK Audit Findings and Opinions on Local Government Financial Performance - Wijayanti, Yulia; Suryandari, Dhini (Accounting Analysis Journal, 2020)
The purpose of this research is to analyze the effect of variables of regional size, regional expenditure, regional wealth level, leverage, government complexity, audit findings and opinion of BPK on the financial performance of local government. The population of this research were 129 District / City in Java and Bali TA. 2014-2015. This research used purposive sampling with 202 samples of the reports of BPK-RI audit results in 2014-2015 and IHPS in 2015-2016 . The analytical tool used in this research was multiple linear regression. The result of this research for variables of regional expenditure and audit opinion have a positive effect, while regional size has a negative effect, the level of regional wealth, leverage, government complexity and audit findings do not affect on the financial performance of the local government. The conclusion of this research is simultaneous testing shows the effect between independent and dependent variables. Size, regional expenditure and audit opinion have significant effect on the financial performance of the local government and the level of regional wealth, leverage, government complexity and audit findings do not have significant affect on the financial performance of the local government.